Prevalence and clinical profile of rotavirus associated diarrhea in a tertiary care center in North India: A descriptive hospital-based study - Gupta, Preeti; Harish, Rekha (Indian Journal of Child Health, 2019)
Background: Rotavirus is the leading cause of severe diarrhea in infancy and childhood period especially in developing countries causing several deaths. Objective: This study was conducted to determine hospital-based prevalence, clinical profile, demographic data, and treatment outcome of rotavirus diarrhea in children under 5 years of age attending a tertiary care hospital in North India. Materials and Methods: A total of 210 patients, under 5 years of age, presenting with a complaint of watery diarrhea were enrolled in the study. Their stool samples were analyzed by latex agglutination test for rotavirus antigen. Significant values of variables were determined using t-tests and Chi-square tests as appropriate. Results: Out of 210 patients, 108 (51.4%) were tested positive for rotavirus. While 170 (80.9%) patients with gastroenteritis were hospitalized, 92 (54.1%) of the hospitalized patients had rotavirus gastroenteritis (RVGE). RVGE was maximum in the season of December (100%), January (92.8%), and February (93.7%). None of the exclusive breastfed patients were tested positive for rotavirus. 75% of the patients with RVGE were top fed and 25% were on mixed feeding. In this study, 79.5% of the patients who were malnourished had RVGE. 54.6% of the patients with RVGE had some dehydration while 35.2% had severe dehydration. The average duration of gastroenteritis (±standard deviation [SD]) in patients with RVGE was 4.30 (0.91) days. Conclusion: The result of the current study reflects that rotavirus is an important cause of severe diarrhea in infants and young children and hence emphasizes the need for the introduction of rotavirus vaccine in the existing national immunization schedule.